Engineering RNA Endonucleases with Customized Sequence Specificities - Choudhury, Rajarshi (2012)
Specific cleavage of RNAs is critical for in vitro manipulation of RNA and for in vivo gene silencing. Here we engineer artificial site-specific RNA endonucleases (ASREs) to function analogously to DNA restriction enzymes. We combine a general RNA cleavage domain with a series of Pumilio/FBF (PUF) domains that specifically recognize different 8-nt RNA sequences. The resulting ASREs specifically recognize RNA substrates and efficiently cleave near their binding sites. ASREs can be devised to recognize and cleave various RNA target sequences, providing a useful tool to manipulate RNAs in vitro. In addition, we generate designer ASREs to specifically silence an endogenous gene in E. coli, as well as a mitochondrial-encoded gene in human cells, suggesting that ASREs can serve as a gene silencing tool with designed specificity.